2023
DOI: 10.1111/codi.16455
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of extraction site incisional hernia after minimally invasive colorectal surgery: a systematic review and meta‐analysis

Abstract: Aim: Minimally invasive colorectal surgery reduces surgical trauma with better preservation of abdominal wall integrity, but the extraction site is still at risk of incisional hernia (IH). The aim of this study was to determine pooled incidence of IH for each type of extraction site and to compare rates of IH after midline, nonmidline and Pfannenstiel extraction.Method: A systematic review and meta-analysis was conducted using the PRISMA guidelines. Single-armed and multiple-armed cohort studies and randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Suprapubic sites and peri‐umbilical sites were subsequently the next two most common extraction sites identified in this study. However, den Hartog et al's 24 meta‐analysis comparing common extraction sites in minimally invasive colorectal procedures demonstrated that nonmidline sites of extraction had significantly fewer incidence of incisional hernia compared with midline sites, without any difference in surgical site infection rates and Pfannenstiel remaining the superior choice in terms of decreased rate extraction site incisional hernia. Although, specimen extraction site can be influenced by a number of factors including anatomical limitations, surgeons' preference, and adherences near site.…”
Section: Discussionmentioning
confidence: 99%
“…Suprapubic sites and peri‐umbilical sites were subsequently the next two most common extraction sites identified in this study. However, den Hartog et al's 24 meta‐analysis comparing common extraction sites in minimally invasive colorectal procedures demonstrated that nonmidline sites of extraction had significantly fewer incidence of incisional hernia compared with midline sites, without any difference in surgical site infection rates and Pfannenstiel remaining the superior choice in terms of decreased rate extraction site incisional hernia. Although, specimen extraction site can be influenced by a number of factors including anatomical limitations, surgeons' preference, and adherences near site.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to alternative extraction sites, the Pfannenstiel incision is deemed superior owing to a much lower risk of incisional hernia [36][37][38]. The extent of the lymphadenectomy within the MIRH for colon cancer is currently a hot topic in the literature, however confusing.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta-analysis showed that the midline extraction site has a 16% incisional hernia rate compared to only 2.1% after the Pfannenstiel incision in minimally-invasive colorectal surgery. 46 In addition, the Pfannenstiel incision is associated with less pain, better cosmetic results, and less wound infection. 47 , 48 Only one study 31 reported the incisional hernia rate, as most studies did not provide complete long-term follow-up information.…”
Section: Discussionmentioning
confidence: 99%